Formation history of tantric texts, their role and importance (Journal of Oriental Studies, 2016)
This article is said about famous Indian mother goddess pantheon Shakti. And also it is considered social role’s of pantheon Shaktiin Indian mythologies and at this time stage era use high point, climax of source.
Keywords: religion; philosophy; the Pantheon; Shactism; Tantra; matriarchy; Puranic era; Bellatrisric era; lyrical explanation; Shiva; Parvat; Kali